2011
DOI: 10.1002/mabi.201100193
|View full text |Cite
|
Sign up to set email alerts
|

Copolymers: Efficient Carriers for Intelligent Nanoparticulate Drug Targeting and Gene Therapy

Abstract: Copolymers are among the most promising substances used in the preparation of drug/gene delivery systems. Different categories of copolymers, including block copolymers, graft copolymers, star copolymers and crosslinked copolymers, are of interest in drug delivery. A variety of nanostructures, including polymeric micelles, polymersomes and hydrogels, have been prepared from copolymers and tested successfully for their drug delivery potential. The most recent area of interest in this field is smart nanostructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 161 publications
0
63
0
Order By: Relevance
“…The microemulsion technique is prepared in ease (with no input of high-energy methods) and provides very low interfacial tension at the oil/water interface, greater solubilization of organic compounds, small droplet size, high surface area, enhanced shelf life, and good thermodynamic stability (18)(19)(20)(21)(22). All these factors enable easy permeation of drugs through small capillary vessels without any discrimination by the host natural defense mechanism and therefore, readily absorbed by the organs presenting improved therapeutic efficacy (23,24). In recent years, there are many findings related to essential oil-based microemulsion system having prospective applications in pharmaceuticals (25)(26)(27)(28)(29).…”
Section: A R T I C L E C Lmentioning
confidence: 99%
“…The microemulsion technique is prepared in ease (with no input of high-energy methods) and provides very low interfacial tension at the oil/water interface, greater solubilization of organic compounds, small droplet size, high surface area, enhanced shelf life, and good thermodynamic stability (18)(19)(20)(21)(22). All these factors enable easy permeation of drugs through small capillary vessels without any discrimination by the host natural defense mechanism and therefore, readily absorbed by the organs presenting improved therapeutic efficacy (23,24). In recent years, there are many findings related to essential oil-based microemulsion system having prospective applications in pharmaceuticals (25)(26)(27)(28)(29).…”
Section: A R T I C L E C Lmentioning
confidence: 99%
“…Manipulating the elasticity and permeability of polymersome membranes can produce high stability in comparison to liposomes and simple lipidbased vesicles formed by low-molecular weight surfactants and lipids. 7,9,10 Furthermore, as a general rule, it is now clearly evident that amphiphilic block copolymers can form vesicles (polymersomes) at the hydrophilic domain to a total mass ratio (ƒ) of about 35%±10%. 11 Previous studies by our group have demonstrated that curcumin encapsulated in dendrosome, a diblock nanostructure made of oleic acid and PEG (400 Da), can kill cancer cells through the apoptosis pathway and significantly reduce tumor size in mice.…”
Section: Introductionmentioning
confidence: 98%
“…Polymer-based nanoparticulate structures used in DDSs are usually derived from dendrimers, micelles, nanoparticles or nanogels, with diameters ranging from 1 to 1000 nm [8,[13][14][15][16][17][18]. Nanocarriers can incorporate a drug through covalent bonding to the polymer, thereby resulting in a polymer-drug conjugate [11,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PEG was shown to provide "stealth", inhibiting fast recognition by the immune systems (i.e., the opsonisation) and minimizing particle aggregation [16,[35][36][37][38][39]. However, the non-biodegradability of this polyether can impedes its application within DDSs.…”
Section: Introductionmentioning
confidence: 99%